Impacts of the energy efficiency law 10.295/2001 in electrical equipment and gas (Research, Society and Development, 2017)
The present study evaluate the impacts of Law 10,295 / 2001, in terms of energy savings, on the following energy consuming equipment: Refrigerators, air conditioners, gas stoves, water heaters, electric motors and compact fluorescent lamps. According to estimates based on energy saving calculations, based on the calculations of the equipment and average consumption of the same for different market conditions (real and baseline), in the year 2010, refrigerators, air conditioners, electric motors and equipment consuming liquefied petroleum gas - LPG (kilns and stoves) the impacts were relatively small, facing the market, with savings of 182.8 GWh, sufficient energy to supply about 120,000 households only. This small impact is justified mainly due to the reduced number of models that have been withdrawn from the market, from all equipment evaluated, since its regulation under the Law.